O feio sacro na imagem de Nossa Senhora das Dores - MORAIS, Aldilene Lopes de (Universidade Federal do Pará, 2020)
This study aims to conduct a study on the sacrum ugly, present in Christian imagery, specifically in the image of Our Lady of Sorrows, which is in the Museum of Sacred Art of BragançaPará (BAM). The image santaapresenta up with the heart outside the body and studded swords. The aim is to then show how was Marian devotion and devotion to the Heart of Mary in the Middle Ages. To visualize the iconography of that holy have the feeling of pity and tenderness. The image-is like something out of the beautiful patterns in this way is considered ugly. In this perspective, to understand how art dealing with Christian concepts is relevant, since the Middle Ages proved to be a period of intense religiosity. We also seek to understand, as the ugliness could be regarded as a good thing, since it caused shock and pity. The image of saints with aspects of suffering could cause gentleness Christians. So our purpose in this paper is to understand the meaning of studded heart and the body of the saint. Umberto Eco, LêniaMongelli and Yara Frateschi, JérômeBaschet and Andrew Vauchez us provide theoretical support for this study.